Expressão heteróloga da quimera LTB/GnRH sintética em Pichia pastoris e seu efeito na resposta imunológica e no epitélio seminífero de camundongos - Pereira, Juliano Lacava (2011)
Several recombinant proteins have been studied as immunocontraception agents in mammals, among them the Gonadotropin-releasing hormone (GnRH). Nevertheless, due to its low molecular weight, GnRH needs to be conjugated with a carrier protein. Among the eukaryotic platforms the yeast Pichia pastoris, which are able of promoting post-translational modifications to expressed recombinant protein. The aim of this study was to clone and express the GnRH/LTB chimera in P. pastoris, and to test it as an immunocontraceptive. In order to accomplish this, sequences of P. pastoris codons usage were synthesized and cloned into the plasmid pPICZαB. The plasmid containing the sequence were propagated and transformed into yeast by electroporation. The transformed colonies were selected by resistance to antibiotics and confirmed by Colony Blotting. The selected clone was cultivated, induced and the protein expressed in supernatant. The protein was concentrated and used as a vaccine antigen. BALB/c males mice were vaccinated twice 15 apart with 100µg de LTB/GnRH adjuvanted with aluminum hydroxide. The immune response was evaluated by ELISA, showing seraconversion in vaccinated animals. The sperm concentration in the control group was 16.93 x 107 and 8.00 x 107 sperm/mL in the immunized group. Vaccination caused a reduction of spermatogenesis (p < 0,05), vacuolization and disorganization of the seminiferous tubules. We concluded that the yeast was able to express the recombinant protein LTB/GnRH, and it demonstrated immunocontraceptive potential in mice.